THE ROLE OF THE TRANSVERSE TECTONIC STRUCTURES OF THE TERRITORY OF THE REPUBLIC OF ARMENIA IN SEISMIC HAZARD ASSESSMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Geological and geophysical data testify to the important role of transversal (near meridional) tectonic dislocations in tectonic structure of the RA territory and adjacent areas. GPS observation data show that maximal horizontal motion and stress concentration also occur in transverse direction. All these indicate the transversal seismogenic fault's activization in assessment of seismic potential of these faults and therefore in compiling the seismic zonation map of the republic.
Keywords: transverse tectonic structures; seismic hazard; transversal seismogenic fault’s